2009
DOI: 10.1108/s0275-4959(2009)0000027016
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in health care among Vietnamese New Orleanians and the impacts of Hurricane Katrina

Abstract: This paper examines the use of routine health care and disparities by socio-economic status among Vietnamese New Orleanians. It also assesses how these differences may have changed as the result of Hurricane Katrina, which struck the Gulf Coast in late summer 2005, devastating the infrastructure of the health care system of New Orleans. Data for this study come from a panel of Vietnamese New Orleanians who were interviewed in 2005, just weeks before the hurricane, and followed up twice near the disaster’s anni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
0
10
1
Order By: Relevance
“…One profound impact is the disruption of traditional networks of social support that communities rely upon to cope with traumatic events. Research in the impacted areas also needs to take into account the unique history and potential strengths and vulnerabilities of ethnic and cultural minorities in the population most affected; for example, Vietnamese fishing communities 202122…”
Section: Mental Health Sequelae Of Previous Oil Spillsmentioning
confidence: 99%
See 1 more Smart Citation
“…One profound impact is the disruption of traditional networks of social support that communities rely upon to cope with traumatic events. Research in the impacted areas also needs to take into account the unique history and potential strengths and vulnerabilities of ethnic and cultural minorities in the population most affected; for example, Vietnamese fishing communities 202122…”
Section: Mental Health Sequelae Of Previous Oil Spillsmentioning
confidence: 99%
“…Research in the impacted areas also needs to take into account the unique history and potential strengths and vulnerabilities of ethnic and cultural minorities in the population most affected; for example, Vietnamese fishing communities. [20][21][22]…”
Section: Mental Health Sequelae Of Previous Oil Spillsmentioning
confidence: 99%
“…These findings also underscore the need to consider the heterogeneity of Hispanic populations in disaster and environmental health disparities research. Intra-ethnic disaster and environmental health disparities have not received much attention in the literature (for exceptions, see 1,27,62,63), and this is particularly problematic in the case of US Hispanic populations, which are growing larger and becoming increasingly heterogeneous. This study revealed substantial intra-ethnic health disparities in El Paso, Texas, which is home to a relatively lowdiversity Hispanic population (almost exclusively white and of Mexican descent).…”
Section: Resultsmentioning
confidence: 97%
“…The participants expressed that refugees did not have much knowledge about how the city delivered emergency training to its general populations, though they and some other Vietnamese refugees had been exposed to some informal training at times, which did not seem to be adequate. Studies done with the Vietnamese communities in New Orleans for the impacts of Hurricane Katrina highlighted the similar disproportionate vulnerabilities that the communities were experiencing and which prevented them from mitigating and recovering from the disaster impacts, such as financial constraint, lack of health insurance and culturally competent health providers, cultural and linguistic isolation, lack of clear and consistent risk communication, and high prevalence of crime within the communities after the disaster (Airriess et al 2008;Chen et al 2007;Do et al 2009;Vu et al 2009). These vulnerabilities were also identified as the risk factors to compromise the Vietnamese New Orleanians' disaster mental health (Norris, VanLandingham, and Vu 2009;Vu and VanLandingham 2012).…”
Section: Discussionmentioning
confidence: 99%